(3GdcGaj aj GdWHs ((3fhQ GdSjQai s)
(3ChdgG (B:s
(3bGd hGVY GdcJGH , ZQV ef gPG GdcJGH JMbjb GdaVdGA dYedi ai GdWH Ydi ChLR s
(3BNQgG (B:s
(3aEPG CUHM TQH eG fbY CaSfJjf (B((3cPG(B) (3bHd GdWYGe , aEfg HOaY VQQ GdMeGQ s
(3eUOQI HagQS eaUd dehVhYGJ GdcJGHs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B- (3U (B152 s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3WH (B88) s
Keywords: (3GdWHs